2020
DOI: 10.1111/jcmm.15854
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin synergizes BRAF‐targeting agent dabrafenib for the treatment of anaplastic thyroid cancer by inhibiting AKT/hTERT signalling

Abstract: As a selective inhibitor of BRAF kinase, dabrafenib has shown potent anti‐tumour activities in patients with BRAFV600E mutant anaplastic thyroid cancer. However, the resistance of thyroid cancer cells to dabrafenib limited its therapeutic effect. The effects of melatonin and dabrafenib as monotherapy or in combination on the proliferation, cell cycle arrest, apoptosis, migration and invasion of anaplastic thyroid cancer cells were examined. The molecular mechanism involved in drug combinations was also reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 49 publications
0
9
0
1
Order By: Relevance
“…As expected, both the apoptotic rate and G0/G1 cell cycle arrest were increased in cells that received combinatorial treatment of melatonin and thapsigargin via triggering ER stress. In fact, melatonin has been shown to exhibit more promising antitumour effect when combining with a wide range of drugs, including dabrafenib, 32 shikonin, 33 valproic acid 17 and cisplatin 34 . These evidences suggested that combinatorial treatment is an effective approach to enhance the capability of melatonin to combat cancer.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, both the apoptotic rate and G0/G1 cell cycle arrest were increased in cells that received combinatorial treatment of melatonin and thapsigargin via triggering ER stress. In fact, melatonin has been shown to exhibit more promising antitumour effect when combining with a wide range of drugs, including dabrafenib, 32 shikonin, 33 valproic acid 17 and cisplatin 34 . These evidences suggested that combinatorial treatment is an effective approach to enhance the capability of melatonin to combat cancer.…”
Section: Discussionmentioning
confidence: 99%
“…There is a large amount of evidence on the benefits of melatonin in anticancer properties including its pro-apoptotic, anti-proliferative, anti-angiogenic, and anti-metastatic properties [ 11 , 12 , 13 ]. Melatonin also has a synergistic effect with different chemotherapeutic drugs [ 14 , 15 , 16 ]. In the clinical study, NSCLC patients concomitantly treated with melatonin exhibited better survival outcomes compared to those treated with chemotherapy alone [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, co-administration of BRAF-directed agents with other drugs, like check point inhibitors (pembrolizumab), may prolong survival of patients [ 152 ]. In in vitro studies, exposure of BRAF V600E-positive ATC cell lines to dabrafenib and melatonin showed synergistic inhibition of hTERT, and in consequence, cell arrest in the G1 phase and decreased cell viability [ 153 ]. Similarly, usage of another SKI, vemurafenib with a STAT3 pathway inhibitor on ATC-derived cell lines (sphere and monolayer) and mouse xenografts resulted in decreased viability and increased rate of cell apoptosis.…”
Section: Currently Used and Investigated Targeted Therapies In Tcsmentioning
confidence: 99%